Oracles, trauma, and the limits of contextualization: naming the witch in contemporary Kenya - Blunt, Robert W. (Journal of Religion in Africa, 2013)
This article revisits Terence Ranger’s call for scholars of the occult in Africa to better historicize, contextualize, and disaggregate the subject. I argue that Ranger’s imperative fails to define what type of object of study the occult is and take seriously the ‘aggregation’ of the occult as an empirical ethnographic fact. I suggest that ‘the occult’ is often experienced as both a proliferating series of oracular institutions for contending with feelings of affliction, and as invisible forces whose origin and nature are compound. I turn to James Siegel’s work on witchcraft to bring attention to the experiential dimension of the occult, and provide an extended ethnographic account of a moment in which the source, nature, and means of redress of an individual’s occult affliction cannot be determined. I argue, in line with Siegel, that historicization and contextualization, while important, risk denaturing the occult and impairing our understanding of its persistence.
free
Keywords: Christianity and African religions; Ethnology – Study and teaching; Kenya – Religion; New Apostolic Church International; Occult sciences; Ranger; Terence; 1929-2015; Siegel; James T; 1937-; Sociology and religion; Witchcraft – Africa